2015
DOI: 10.1007/s10802-015-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Informed Cross-Lagged Analysis of Autistic-Like Traits and Affective Problems in Early Childhood

Abstract: A genetically informed cross-lagged model was applied to twin data to explore etiological links between autistic-like traits and affective problems in early childhood. The sample comprised 310 same-sex twin pairs (143 monozygotic and 167 dizygotic; 53% male). Autistic-like traits and affective problems were assessed at ages 2 and 3 using parent ratings. Both constructs were related within and across age (r = .30−.53) and showed moderate stability (r = .45−.54). Autistic-like traits and affective problems showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Consistent with Micalizzi et al (2016), results of the present study indicate that social communicative autistic impairment and general psychopathologic impairment are separable developmental domains with distinct genetic etiologies. Additionally, our results suggest that associations between autistic and psychopathologic traits strengthen over the course of early development (i.e., 18 to 36 months), bridging research in older samples that demonstrated strong correlations between degree of autistic impairment and degree of internalizing (Hallett et al, 2012) and externalizing (Ronald et al, 2010; Taylor et al, 2013) behaviors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with Micalizzi et al (2016), results of the present study indicate that social communicative autistic impairment and general psychopathologic impairment are separable developmental domains with distinct genetic etiologies. Additionally, our results suggest that associations between autistic and psychopathologic traits strengthen over the course of early development (i.e., 18 to 36 months), bridging research in older samples that demonstrated strong correlations between degree of autistic impairment and degree of internalizing (Hallett et al, 2012) and externalizing (Ronald et al, 2010; Taylor et al, 2013) behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…The utility of the CBCL for ascertaining the characterizing traits and features of autism is somewhat limited, however, because it only captures a fraction of the variance captured by more specific assessment of autistic traits (see Bölte, Poustka, & Constantino, 2008). Micalizzi, Ronald, & Saudino (2016) used a cross-lagged twin design to evaluate the time course of associations between autistic traits (here again, the CBCL Pervasive Developmental Problems scale was used) and affective problems (CBCL Affective Problems scale) during the third year of life. They observed substantial correlations between autistic traits and affective problems, which were attributable to shared and nonshared environmental influences at age 2 and genetic influences at age 3.…”
mentioning
confidence: 99%
“…Importantly, in the ASD group, the association between distress intensity and autism severity was negligible, regardless of the type of threat. The latter finding is consistent with studies suggesting that fear responses and social deficits are not mediated by the same circuitry in the amygdala [Emery et al, 2001; Emery & Amaral, 2000; Prather et al, 2001] and with evidence from genetic twin studies highlighting etiologic independence of autistic‐like traits and precursors of later affective and behavioral psychopathology [Hawks et al, 2019; Micalizzi et al, 2016]. The findings are also consistent with prior parent‐report and experimental studies, which indicate that negative (fear and frustration) affectivity does not track with severity of autism symptoms in infants [Paterson et al, 2019], toddlers [Macari et al, 2017; Macari et al, 2018], and older children with ASD [Herrington et al, 2017; Konstantareas & Stewart, 2006].…”
Section: Discussionsupporting
confidence: 86%
“…This idea is based on studies in the general population examining links between autistic‐like or social traits and precursors of later psychopathology. For instance, a study investigating autistic and affective features in a prospective sample of 2‐ and 3‐ year‐old twins demonstrated high cross‐age stability of the traits but negligible cross‐lagged effects, suggesting that early in development, there is a limited contribution of autistic‐like traits to affective traits and vice versa [Micalizzi et al, 2016]. Similarly, a study of 18 month olds demonstrated very weak intercorrelations between social characteristics and internalizing and externalizing behaviors and an increasing cross‐lagged association by the age of 3 [Hawks et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation